The factors influence corporate social responsibility (CSR) performance in Telekom Malaysia Berhad (TM SME) / Norhafiza Sudin - Sudin, Norhafiza (2014)
This study was carried out to identify the factors that influence corporate social responsibility (CSR) performance in Telekom Malaysia Berhad (TM SME). In chapter one, the researcher discussed about the background of the study. This research is study about the activities in CRS as the independent variables toward the CSR performance as the dependent variables. The objectives of this study arc to identify either economic responsibility influence corporate social responsibility (CSR) in the organization, to identify either ethical responsibility influence corporate social responsibility (CSR) in the organization, to identify either philanthropy responsibility influence corporate social responsibility (CSR) in the organization and to identify the factors influence corporate social responsibilities (CSR) performance in organization. For the chapter three, methodology use for this research has been discussed. The methodology is method used by the researcher in finding the result while completing this research. This is including research design, sampling frame, population. sampling technique, and sample size, unit of analysis, instrument. and validity of instrument, data collection procedures and plan of data analysis. The researcher use stratified sampling technique. The scope of study only revolves within the organization and chooses workers from the certain department as respondent for the research. The researcher chooses workers from Telekom Malaysia (TM SME) as a scope of the study.